High D-dimer levels in patients with Takotsubo syndrome: 2.5 years follow-up. (14th October 2021) - Biccire, F G; Pastori, D; Cardillo, I; Chianta, V; Ferrari, I; Debelak, C; Pannarale, G; Torromeo, C; Gaudio, C; Barilla, F; Tanzilli, G
Abstract: Background: Takotsubo syndrome (TTS) was initially described as an acute reversible left ventricular (LV) dysfunction associated with emotional trigger and good prognosis. However, several clinical conditions and physical stresses have recently been reported to favor episodes of TTS. Besides myocardial stunning and endothelial dysfunction, a pro-inflammatory status represents a critical point in TTS patients. D-dimer, a specific metabolite of cross-linked fibrin, has recently been proposed as a prognostic tool in critical patients for its connection to proinflammatory and coagulation state. Purpose: The aim of our study was to evaluate whether high D-dimer levels at admission were related to disease severity and worse outcomes at mid-term follow-up in TTS patients. Methods: We retrospectively analysed clinical, laboratory, echocardiographic (left ventriucular ejection fraction, LVEF) and angiographic characteristics of 40 consecutive cases of TTS admitted to our department from January 2016. Elevated circulating D-dimer levels (defined as >550 μg/l) were correlated with characteristics of patients, in-hospital major adverse cardiac events (MACE, defined as the composite of acute pulmonary oedema, cardiogenic shock, sustained ventricular tachycardia, ventricular fibrillation, cardiac arrest or death) and mortality at 2.5 year follow-up. Results: Of 40 patients with Takotsubo syndrome, 38 completed 2.5 years follow-up. All patients were women, with a mean age of 69.5±13.9 years. High D-dimer levels were detected in 21 patients (55.3%). Similar age, cardiovascular risk factors and angiographic findings were found between two groups. Patients with high D-dimer levels were more frequently associated with reduced LVEF (<40%) at discharge (23.8% vs 0%, p=0.041) and in-hospital MACE (33.3% vs 5.9%, p=0.045). Furthermore, high D-dimer levels significantly correlated with admission C-reactive protein and high-sensitive troponin T values (rS 0.570, p<0.001 and rS 0.433, p=0, 007, respectively) and first LVEF% (rS −0.358 p=0.028). At mean of 2.5-year follow-up, 6 patients died. Patients who died were significantly older (81.3±5.3 vs 67.2±14.1, p=0.010) and with higher admission GRACE score (131.4±9.4 vs 101.5±25.6, p=0.003) than patients who survived. Moreover, higher admission D-dimer levels (28.6% vs 0%, p=0.020), physical trigger (66.7% vs 21.9%, p=0047) and discharge LVEF<40% (66.7% vs 15.6%, p=0.020) were significantly more frequently among patients who died. Conclusions: Elevated circulating D-dimer levels at admission for TTS were associated with higher mortality rate at 2.5 years follow-up, along with physical trigger and depressed LVEF at discharge. Moreover, high D-dimer levels were associated with in-hospital higher incidence of MACE and depressed LVEF. These results support the hypothesis that different pathophysiological mechanisms may be implicated in LV dysfunction in TTS, leading to different prognosis. Funding Acknowledgement: Type of funding sources: None.